2001
DOI: 10.1103/physrevlett.87.196101
|View full text |Cite|
|
Sign up to set email alerts
|

Shape of a Liquid Front upon Dewetting

Abstract: We examine the profile of a liquid front of a film that is dewetting a solid substrate. Since volume is conserved, the material that once covered the substrate is accumulated in a rim close to the three phase contact line. Theoretically, such a profile of a Newtonian liquid resembles an exponentially decaying harmonic oscillation that relaxes into the prepared film thickness. For the first time, we were able to observe this behavior experimentally. A non-Newtonian liquid -a polymer melt -however, behaves diffe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
58
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(65 citation statements)
references
References 19 publications
6
58
1
Order By: Relevance
“…The slopes of the lines agree with the negative real eigenvalue of with the smallest modulus of (4.4). Interestingly, dewetting ridges with similar profiles have been observed experimentally for highly elastic and long-chain polymer films [34,35].…”
Section: Evolution Of Profiles In Timementioning
confidence: 63%
“…The slopes of the lines agree with the negative real eigenvalue of with the smallest modulus of (4.4). Interestingly, dewetting ridges with similar profiles have been observed experimentally for highly elastic and long-chain polymer films [34,35].…”
Section: Evolution Of Profiles In Timementioning
confidence: 63%
“…We now describe the ultimate behaviour of the film profile for (32)(33). From (52) and (56) it is clear that the above separation of length scales becomes invalid for…”
Section: Formulationmentioning
confidence: 98%
“…For brevity we present the asymptotic derivation in a somewhat ad hoc manner; we stress that it can be made fully systematic. For experimental results with which the resulting rim profiles can be compared, see [33] for example.…”
Section: Newtonian Fluids; M = 1 N =mentioning
confidence: 99%
See 1 more Smart Citation
“…Such depressions have been observed in several works, and their appearance has also been accounted for in simulations [24,25]. Their presence has been explained as a consequence of material flow and thickness fluctuations [26,27]. Also, it has been shown that, when a hole in a dewetting film has reached a certain size, secondary or "satellite" holes appear in the depression [28,29].…”
Section: Resultsmentioning
confidence: 90%